(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article is dedicated to the improvement of the teaching methodology based on the integrative approach based on the application of non-standard assignments from the physics course, selection and application to the educational process in the formation of the professional training of future pedagogues in the higher educational institutions of pedagogy, developing the level of knowledge of students, expanding the scope of their thinking. , reflection of interdisciplinarity, interest in science and development of professional training are important. The methodical system of science is improved in students by reviewing problems, tests and non-standard assignments in the development of physics, geography, biology, chemistry and inter-subject connections.